Laser-Induced Fluorescence Studies on Some Edible Oils and Aromatic Frankincense Oil Excited by Blue and Violet Diode Lasers at 447 nm and 405 nm - Abedin, Kazi Monowar (Journal of Spectroscopy, 2022)
Laser-induced fluorescence (LIF) of certain edible oils (olive, mustard, sunflower, corn, sesame, peanut, rice bran, and flaxseed) and one unique aromatic oil (frankincense oil) have been studied using compact blue and violet lasers operating at 447 nm and 405 nm, respectively. LIF studies excited at these wavelengths have not been performed before, to our knowledge. The various features of the obtained spectra and their possible molecular origins have been discussed. The presence of vitamin E has been confirmed in corn, rice bran, peanut, sunflower, and frankincense oils, and the possible origin of the double peaks in the red region for olive oil has been explained.